A 5XXX aluminum alloy and its preparation method and application

By optimizing the composition and processing technology of 5XXX aluminum alloy, the tolerance to impurity elements and the strength and formability of aluminum alloy are improved, and the insufficient performance of recycled aluminum alloys in the field of deformed aluminum alloys is solved, and efficient carbon emission reduction effect is achieved.

CN118957369BActive Publication Date: 2025-03-11WEIQIAO LIGHTWEIGHT RESEARCH CENTER AT SOOCHOW

Patent Information

Application Number
CN202411194592.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-03-11
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

In the prior art, the application of recycled aluminum alloys in the field of deformed aluminum alloys has problems of insufficient strength and forming performance, especially the low tolerance for impurity elements such as Fe, Mn, Si, etc., which leads to a decrease in alloy performance.

Method used

By optimizing the composition of 5XXX aluminum alloy, the content of Fe and Mn elements is increased, and Sr, Mo and Be microalloyed elements are added, combined with homogenization treatment, hot rolling and cold rolling processing technology, the grain size and second phase morphology are adjusted, and the tolerance and performance of the alloy are improved.

Benefits of technology

It achieves high tolerance for impurity elements such as Fe, Mn, Si, etc., improves the strength and formability of aluminum alloys, is suitable for applications such as car body inner panels, structural parts or rail transit tools, and has good recyclability and reduces carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118957369B_ABST
    Figure CN118957369B_ABST
Patent Text Reader

Abstract

The present invention relates to a 5XXX aluminum alloy and a preparation method and application thereof. In terms of mass percentage, the 5XXX aluminum alloy includes Si 0.1-0.4%, Fe 0.35-0.6%, Cu 0.05-0.3%, Mn 0.4-0.9%, Mg 3.5-5.0%, Cr 0.05-0.3%, Zn 0-0.25%, Sr 0.01-0.15%, Mo 0.01-0.15%, Be 0-0.001%, Ti≤0.15%, other impurities≤0.15%, and the remainder is Al. The 5XXX aluminum alloy of the present application still shows high strength and excellent formability under high Fe and Mn element contents. The 5XXX aluminum alloy of the present application can be prepared using recycled aluminum alloy, and itself has very good recyclable recovery capacity, and has great advantages in reducing carbon emissions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of aluminum alloy and aluminum plate and strip processing, and in particular to a 5XXX aluminum alloy and a preparation method and application thereof. Background Art

[0002] This section is intended to provide a background or context to the embodiments of the invention recited in the claims. No admission is made that the description herein is prior art by inclusion in this section.

[0003] 5XXX series aluminum alloy is a type of aluminum alloy with magnesium as the main alloying element, and the magnesium content is usually between 3 and 5%. It has good weldability, formability, corrosion resistance and medium strength, and is widely used in rail transportation, automobiles, ships and other fields.

[0004] There are many studies on 5XXX series aluminum alloys in the prior art, as follows:

[0005] Patent CN106834825A discloses a 5182 aluminum alloy and a process for preparing the aluminum alloy into a can cover strip material, which is composed of the following components by weight percentage: Si: ≤0.1%, Fe: ≤0.2%, Cu: 0.04-0.07%, Mn: 0.3-0.4%, Mg: 4.5-4.8%, Cr: ≤0.05%; Zn: ≤0.05%, Ti: 0.014-0.04%, and the rest are Al and some inevitable impurity elements. The alloy strength is improved by high alloying, while the Fe and Si contents are reasonably controlled to inhibit the generation of material lines; continuous air cushion furnace annealing is adopted, and the grain size is regulated by high temperature and short time annealing to improve the uniformity of strip performance and ensure the surface quality of the strip.

[0006] Patent CN118360521A discloses a high-strength and high-elongation 5182 aluminum alloy and its manufacturing method, which contains the following chemical elements in mass percentage: Si: 0.05~0.15%, Fe: 0.20~0.30%, Cu: 0.05~0.08%, Mn: 0.30~0.40%, Mg: 4.8~5.0%, Cr: 0.02~0.09%, Ti: 0.015~0.025%. Through chemical composition design and optimized manufacturing process, high strength and high elongation are obtained.

[0007] Patent CN113462936A discloses an aluminum alloy can pull ring and its processing technology. The aluminum alloy can pull ring is punched out of 5182 aluminum alloy. The weight percentage of each element in 5182 aluminum alloy is: Si: ≤0.08%, Fe: ≤0.25%, Cu: ≤0.1%, Mn: 0.2~0.3%, Mg: 4.4~4.6%, Cr: ≤0.05%, Zn: ≤0.15%, other single impurities ≤0.03%, total impurities ≤0.15%, and the balance is Al. It is made by melting, sawing, soaking, hot rolling, cold rolling, stretching, bending and straightening.

[0008] However, these patents do not use recycled aluminum as the main raw material, while aluminum alloy has extremely high recycling value. Compared with electrolytic aluminum, the energy consumption for producing 1 ton of recycled aluminum is only about 5% of that of electrolytic aluminum, which has significant advantages in reducing carbon footprint.

[0009] However, recycled aluminum alloys inevitably contain a large amount of Fe, Si, and Mn elements. To ensure the strength of the alloy, the Mg content is generally above 3.5wt.%, so the solubility of impurity elements such as Fe, Mn, and Si in the aluminum matrix is ​​further reduced. Therefore, a large amount of Fe, Si, and Mn elements form coarse Al in the aluminum alloy. x (Fe, Mn), Al(Fe, Mn)Si, Mg2Si and other second phases, and present complex morphologies such as fishbone and flower shapes. These coarse second phases are extremely difficult to fully crush or dissolve, and remain in the final aluminum alloy product, seriously reducing the strength and formability of the alloy.

[0010] At present, the application of recycled aluminum alloys in the field of deformed aluminum alloys is mainly 8XXX or 1XXX aluminum alloys with a low degree of alloying, and it is necessary to add expensive rare earth elements such as La, Ce, Sc to weaken the reduction in plasticity caused by the coarse iron-rich phase. For example, patent CN1177778821A improves the plasticity of the recycled aluminum alloy and refines the iron-rich phase morphology by adding 0.5% or more La to the recycled aluminum alloy and improving the casting and rolling method.

[0011] Patent CN116790947A discloses a 5086 recycled aluminum alloy automotive sheet and its production method, the alloy includes: Si 0.04%~0.35%, Fe 0.10%~0.35%, Cu≤0.10%, Mn 0.20%~0.50%, Mg 3.6%~4.1%, Cr≤0.15%, Zn≤0.20%, Ti≤0.10%, other single impurities≤0.05%, other impurities total amount≤0.15%, the rest is Al. However, the Fe content in this patent needs to be controlled below 0.35%, so some electrolytic aluminum needs to be added, and the Rm of the O-state 5086 recycled aluminum alloy is up to 281MPa, R p0.2The highest is 131MPa. The raw materials of its recycled 5086 aluminum alloy only come from the process waste of aluminum plants and automobile OEMs. The source is single and the market holdings are limited. In addition, the use cycle of aluminum alloys of OEMs is long, which undoubtedly prolongs the entire cycle of recycled aluminum alloys from recycling-plate processing-use-recycling, making it difficult to meet the needs of large-scale recycling. And according to the raw materials of its recycled aluminum alloy, it can only achieve the grade-keeping utilization of aluminum for automobiles, and cannot use low-quality recycled aluminum alloys such as can materials with higher Fe content.

[0012] In summary, the aluminum products made from recycled aluminum can only be used to maintain their grade at best, and most of them are downgraded. Therefore, it is still necessary to develop a 5XXX aluminum alloy with high tolerance to impurity elements such as Fe, Mn, Si and good mechanical properties. Summary of the invention

[0013] The object of the present invention is to provide a 5XXX aluminum alloy having high tolerance to impurity elements such as Fe, Mn, Si and the like and good mechanical properties, and a preparation method and application thereof.

[0014] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0015] A first aspect of the present invention provides a 5XXX aluminum alloy, which includes, by mass percentage, Si 0.1-0.4%, Fe 0.35-0.6%, Cu 0.05-0.3%, Mn 0.4-0.9%, Mg 3.5-5.0%, Cr 0.05-0.3%, Zn 0-0.25%, Sr0.01-0.15%, Mo 0.01-0.15%, Be 0-0.001%, Ti≤0.15%, other impurities≤0.15%, and the balance is Al.

[0016] According to some specific embodiments, it includes, by mass percentage, Si 0.2-0.3%, Fe 0.4-0.55%, Cu 0.05-0.3%, Mn 0.45-0.85%, Mg 3.5-4.5%, Cr 0.05-0.3%, Zn 0-0.25%, Sr 0.01-0.15%, Mo 0.01-0.15%, Be 0-0.001%, Ti≤0.15%, other impurities≤0.15%, and the balance is Al.

[0017] According to some specific embodiments, the mass percentage of Sr is 0.02-0.1%, for example, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09% or 0.1%, the mass percentage of Mo is 0.02-0.1%, for example, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09% or 0.1%, and the mass percentage of Be is 0.0001-0.001%, for example, 0.0001%, 0.0002%, 0.0003%, 0.0004%, 0.0005%, 0.0006%, 0.0007%, 0.0008%, 0.0009% or 0.001%.

[0018] According to some specific embodiments, the total mass percentage of the Sr and the Mo does not exceed 0.15%.

[0019] According to some specific embodiments, the total mass percentage of the Mn, the Mg and the Cu is ≥ 4%.

[0020] According to some specific embodiments, the mass ratio of the total mass of the Mn and the Cr to the Fe is 1:1~3:1, for example, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, and 3:1.

[0021] According to some specific embodiments, the mass ratio of the total mass of the Sr and the Mo to the Si is 1:20-1:1.5, and further, the mass ratio of the total mass of the Sr and the Mo to the Si is 1:1.5-1:5, for example, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2 .5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, 1:3, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9, 1:4, 1:4.1, 1:4.2, 1:4.3, 1:4.4, 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9, 1:5.

[0022] According to some specific embodiments, the mass percentage of each of the other impurities is ≤0.05%.

[0023] According to some specific embodiments, the tensile strength Rm of the 5XXX aluminum alloy is ≥ 330 MPa, and the plastic extension strength R p0.2 ≥180MPa, elongation after fracture A 50 ≥22%.

[0024] According to some specific embodiments, the average equivalent diameter of the iron-rich phase in the 5XXX aluminum alloy is ≤ 1.6 μm.

[0025] According to some specific embodiments, the 5XXX aluminum alloy is an O-state aluminum alloy.

[0026] A second aspect of the present invention provides a method for preparing the 5XXX aluminum alloy, comprising the following steps:

[0027] (1) Using waste aluminum as raw material, selectively adding one or more of Al-Mn, Al-Cr, Al-Mo, Mg ingots, Al-Sr, and Al-Be master alloys, and sequentially performing smelting, slagging, alloying, refining, and casting to obtain aluminum alloy ingots;

[0028] (2) homogenizing the aluminum alloy ingot, controlling the homogenization temperature to be 420-480° C., and holding the temperature for 2-12 hours;

[0029] (3) hot rough rolling the aluminum alloy ingot after homogenization treatment, and controlling the deformation to be greater than 86%;

[0030] (4) hot finishing rolling the hot rolled material after hot rough rolling, and controlling the deformation to be greater than 80%;

[0031] (5) cold rolling the hot rolled material after hot finishing rolling, and controlling the deformation amount to 65~93%;

[0032] (6) Annealing the cold-rolled material to obtain the 5XXX aluminum alloy.

[0033] According to some specific embodiments, the waste aluminum is one or more of recycled cans, automobile plates, and ship plates.

[0034] Among them, cans are mainly 3XXX and 5XXX aluminum alloys, while automobile plates and ship plates are mainly 5XXX and 6XXX aluminum alloys. In addition to recycled cans, automobile plates, ship plates, etc., the scrap aluminum in this application can also be one or more of 3XXX aluminum alloys, 5XXX aluminum alloys, and 6XXX aluminum alloys from other sources.

[0035] According to some specific implementations, in step (3), the hot rough rolling has 16 to 22 passes.

[0036] According to some specific embodiments, in step (4), the final rolling temperature of the hot finishing rolling is controlled to be greater than 310°C.

[0037] According to some specific embodiments, in step (6), the annealing step is performed in a box annealing furnace or an air cushion continuous annealing furnace.

[0038] Furthermore, when annealing is performed in the box-type annealing furnace, the temperature is controlled to be 300-380°C and the holding time is 2-6h; when annealing is performed in the air cushion continuous annealing furnace, the temperature is controlled to be 440-500°C and the holding time is 0s-120s.

[0039] According to some specific embodiments, in step (1), the area percentage of the iron-rich phase in the aluminum alloy ingot is controlled to be ≤3.5%, and the average equivalent diameter is ≤3.5 μm; the area percentage of the Mg2Si phase is controlled to be ≤1.6%, and the average equivalent diameter is controlled to be ≤1.2 μm.

[0040] A third aspect of the present invention provides a use of the 5XXX aluminum alloy, or the 5XXX aluminum alloy prepared by the preparation method, in automobile body inner panels, structural parts or rail transit structural parts.

[0041] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0042] Compared with the traditional high-strength 5XXX aluminum alloy, the 5XXX aluminum alloy of the present application has a high content of Fe and Mn elements, that is, the 5XXX aluminum alloy of the present application has a high tolerance to impurity elements such as Fe and Mn. Moreover, the 5XXX aluminum alloy of the present application still exhibits high strength and excellent formability at high Fe and Mn content, and can be used in automobile body inner panels, structural parts or rail transportation fields.

[0043] The 5XXX aluminum alloy of the present application can be prepared using recycled aluminum alloy, and has very good recyclability, which has great advantages in reducing carbon emissions. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 is the as-cast structure diagram of the aluminum alloy ingot of Comparative Example 1;

[0045] Figure 2 is the as-cast structure diagram of the aluminum alloy ingot of Comparative Example 3;

[0046] Figure 3 is a cast structure diagram of the aluminum alloy ingot of Example 1;

[0047] Figure 4 is a cast structure diagram of the aluminum alloy ingot of Example 2;

[0048] Figure 5 is a cast structure diagram of the aluminum alloy ingot of Example 3;

[0049] Figure 6 is a cast structure diagram of the aluminum alloy ingot of Example 4;

[0050] Figure 7 is a cast structure diagram of the aluminum alloy ingot of Example 5;

[0051] Figure 8 is a cast structure diagram of the aluminum alloy ingot of Example 6;

[0052] Fig. 9 is the as-cast structure diagram of the aluminum alloy ingot of Example 7;

[0053] Fig.10 This is the statistical result of the percentage of Fe-rich phase area in the alloy cast structure;

[0054] Fig.11 This is the statistical result diagram of the equivalent diameter of the Fe-rich phase in the alloy cast structure;

[0055] Fig.12 This is the statistical result of the area percentage of Mg2Si phase in the alloy cast structure;

[0056] Fig.13 This is the statistical result diagram of the equivalent diameter of the Mg2Si phase in the alloy cast structure;

[0057] Fig.14 This is the metallographic structure diagram of the ingot after homogenization treatment in Comparative Example 1;

[0058] Fig.15 This is the metallographic structure diagram of the ingot after homogenization treatment in Comparative Example 2;

[0059] Fig.16 This is the metallographic structure diagram of the ingot after homogenization treatment in Comparative Example 3;

[0060] Fig.17 The metallographic structure diagram of the ingot after homogenization treatment of Comparative Example 4;

[0061] Fig.18 This is the metallographic structure diagram of the ingot after homogenization treatment in Example 1;

[0062] Fig.19 This is the metallographic structure diagram of the ingot after homogenization treatment in Example 2;

[0063] Fig. 20 This is the metallographic structure diagram of the ingot after homogenization treatment in Example 3;

[0064] Fig.21 This is the metallographic structure diagram of the ingot after homogenization treatment in Example 4;

[0065] Fig. 22This is the metallographic structure diagram of the ingot after homogenization treatment in Example 5;

[0066] Fig.23 This is the metallographic structure diagram of the ingot after homogenization treatment in Example 6;

[0067] Fig.24 This is the metallographic structure diagram of the ingot after homogenization treatment in Example 7;

[0068] Fig.25 This is a statistical result chart of the equivalent diameter of the iron-rich phase in the aluminum alloy after rolling. DETAILED DESCRIPTION

[0069] Since the existing technology of using recycled aluminum to manufacture aluminum products has the problem that the highest grade can only be maintained, and most of them are downgraded, and the tolerance to iron is low, it is usually still necessary to limit the iron content to below 0.35% to ensure the performance of the manufactured aluminum alloy. To this end, the application discloses a manufacturing method and application of a high-strength Al-Mg alloy with high Fe and Mn content and its plate, the alloy can be produced using recycled materials such as can materials, has high strength and good formability, and the alloy itself is highly recyclable and has significant advantages in reducing the carbon emissions of aluminum alloys.

[0070] Since the performance of aluminum alloys mainly depends on the alloy composition, the alloy composition directly determines the most basic properties of the alloy, such as mechanical properties, forming properties, etc. Therefore, the present application changes the precipitation behavior of the α-Al matrix and the second phase of the aluminum alloy during the solidification process by controlling the composition, reducing the content of the Mg element, controlling the upper limit of the addition of Mn and Cr elements, and adding Sr, Mo, and Be micro-alloying elements. The grain size and the morphology, quantity, and size of the iron-rich phase are regulated, and the control of the homogenization treatment, hot rolling, and cold rolling processing technology is assisted to fully crush the coarse second phase particles, and the final product microstructure and performance are regulated in combination with the final annealing process. Finally, the tolerance of the alloy to impurity elements such as Fe, Mn, and Si is improved, and the alloy has a good match between strength and plasticity.

[0071] Among them, the present application can use a high proportion of recycled aluminum alloy as raw material, and only needs to use a small amount of Al-Mn, Al-Cr, Al-Mo, Mg ingots, Al-Sr, Al-Be master alloys to adjust the quality of each element in the aluminum alloy. In some embodiments, the ratio of recycled aluminum alloy to the total amount of raw materials is more than 70%.

[0072] The present invention is further described below in conjunction with the examples. However, the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0073] Unless otherwise specified herein, the preparation methods involved in the following examples or comparative examples refer to the prior art. Comparative Example 1

[0074] This example provides an AA5182 alloy and a preparation method thereof, wherein the alloy composition meets the AA standard 5182 alloy composition requirements. In terms of mass percentage, the AA5182 alloy contains 0.15% Si, 0.2% Fe, 0.1% Cu, 0.35% Mn, 0.05% Cr, 4.5% Mg, 0.15% Zn, 0.02% Ti, other unavoidable impurities and the balance Al.

[0075] The preparation method of the alloy comprises the following steps:

[0076] (1) Using electrolytic aluminum ingots or electrolytic aluminum liquid as raw materials, the raw materials are melted in a smelting furnace at a melting temperature of 760°C, and then slag removal, alloying, refining, and casting are carried out in sequence to obtain aluminum alloy ingots with target aluminum alloy composition.

[0077] (2) The aluminum alloy ingot obtained in step (1) is subjected to homogenization treatment, and the homogenization treatment temperature is controlled to be 460° C. and the holding time is 8 h.

[0078] (3) The ingot after homogenization treatment is subjected to hot rough rolling, the hot rolling start temperature is controlled at 440°C, and the ingot is hot rolled to an intermediate billet through 18 passes, and the hot rough rolling deformation is 91%.

[0079] (4) The intermediate billet after hot rough rolling is subjected to hot finish rolling, and the hot finish rolling deformation is controlled to be 93% and the final rolling temperature is 320°C.

[0080] (5) The hot-rolled coil is cold rolled to 1.2 mm, with a cold rolling deformation of 82%.

[0081] (6) The cold-rolled coil is annealed in a box-type annealing furnace at a controlled temperature of 340°C for 4 hours to obtain a final product in the O state. Comparative Example 2

[0082] This example is basically the same as comparative example 1, except for the temperature and time of the homogenization treatment in step (2). The homogenization treatment temperature in this example is 480° C. and the holding time is 6 hours. Comparative Example 3

[0083] This example provides a B1 alloy and a preparation method thereof. Calculated by mass percentage, the B1 alloy contains 0.25% Si, 0.45% Fe, 0.1% Cu, 0.8% Mn, 0.05% Cr, 4.5% Mg, 0.15% Zn, 0.02% Ti, other inevitable impurities and the balance Al.

[0084] The preparation method of the alloy comprises the following steps:

[0085] (1) The recycled can material is used as raw material to be smelted in a smelting furnace at a melting temperature of 760°C. After refining and slagging, a component pre-analysis test is performed. According to the result of the component pre-test, Al-Mn, Al-Cr, and Mg ingot intermediate alloys are added to alloy according to the element composition of the present invention to obtain an aluminum alloy melt with qualified composition. Then, slagging, alloying, refining, slagging, and casting are performed in sequence to obtain an aluminum alloy ingot with a target aluminum alloy composition.

[0086] (2) The aluminum alloy ingot obtained in step (1) is subjected to homogenization treatment, and the homogenization treatment temperature is controlled to be 460° C. and the holding time is 8 h.

[0087] (3) The ingot after homogenization treatment is subjected to hot rough rolling, the hot rolling start temperature is controlled at 440°C, and the ingot is hot rolled to an intermediate billet through 18 passes, and the hot rough rolling deformation is 91%.

[0088] (4) The intermediate billet after hot rough rolling is subjected to hot finish rolling, and the hot finish rolling deformation is controlled to be 93% and the final rolling temperature is 320°C.

[0089] (5) The hot-rolled coil is cold rolled to 1.2 mm, with a cold rolling deformation of 82%.

[0090] (6) The cold-rolled coil is annealed in a box-type annealing furnace at a controlled temperature of 340°C for 4 hours to obtain a final product in the O state. Comparative Example 4

[0091] This example is basically the same as comparative example 3, except for the temperature and time of the homogenization treatment in step (2). The homogenization treatment temperature in this example is 480° C. and the holding time is 6 hours. Example 1

[0092] This example provides a B2 alloy and a preparation method thereof. Calculated by mass percentage, the B2 alloy contains 0.25% Si, 0.45% Fe, 0.1% Cu, 0.8% Mn, 0.05% Cr, 4.2% Mg, 0.15% Zn, 0.02% Ti, 0.05% Sr, 0.05% Mo, 0.0005% Be, other inevitable impurities and the balance Al.

[0093] The preparation method of the alloy comprises the following steps:

[0094] (1) The recycled can material is used as raw material to be smelted in a smelting furnace at a melting temperature of 760°C. After refining and slagging, a component pre-analysis test is performed. According to the result of the component pre-test, Al-Mn, Al-Cr, Al-Mo, Mg ingots, Al-Sr, and Al-Be master alloys are added according to the element composition of the present invention to obtain an aluminum alloy melt with qualified composition. Then, slagging, alloying, refining, slagging, and casting are performed in sequence to obtain an aluminum alloy ingot with a target aluminum alloy composition.

[0095] (2) The aluminum alloy ingot obtained in step (1) is subjected to homogenization treatment, and the homogenization treatment temperature is controlled to be 420° C. and the holding time is 10 h.

[0096] (3) The ingot after homogenization treatment is subjected to hot rough rolling, the hot rolling start temperature is controlled at 440°C, and the ingot is hot rolled to an intermediate billet through 18 passes, and the hot rough rolling deformation is 91%.

[0097] (4) The intermediate billet after hot rough rolling is subjected to hot finish rolling, and the hot finish rolling deformation is controlled to be 93% and the final rolling temperature is 320°C.

[0098] (5) The hot-rolled coil is cold rolled to 1.2 mm, with a cold rolling deformation of 82%.

[0099] (6) The cold-rolled coil is annealed in a box-type annealing furnace at a controlled temperature of 340°C for 4 hours to obtain a final product in the O state. Example 2

[0100] This example is basically the same as Example 1, the only difference being the aluminum alloy composition and the temperature and time of the homogenization treatment in step (2).

[0101] Measured in percentage by mass, the B3 alloy provided in this example contains 0.25% Si, 0.45% Fe, 0.15% Cu, 0.8% Mn, 0.05% Cr, 3.5% Mg, 0.15% Zn, 0.02% Ti, 0.05% Sr, 0.1% Mo, 0.0005% Be, other unavoidable impurities and the balance Al.

[0102] The homogenization treatment temperature in this example is 430° C. and the holding time is 8 h. Example 3

[0103] This example is basically the same as Example 1, the only difference being the aluminum alloy composition and the temperature and time of the homogenization treatment in step (2).

[0104] Measured in percentage by mass, the B4 alloy provided in this example contains 0.25% Si, 0.45% Fe, 0.15% Cu, 0.85% Mn, 0.05% Cr, 4% Mg, 0.2% Zn, 0.02% Ti, 0.05% Sr, 0.05% Mo, 0.0005% Be, other unavoidable impurities and the balance Al.

[0105] The homogenization treatment temperature in this example is 440° C. and the holding time is 12 h. Example 4

[0106] This example is basically the same as Example 1, the only difference being the aluminum alloy composition and the temperature and time of the homogenization treatment in step (2).

[0107] Measured in percentage by mass, the B5 alloy provided in this example contains 0.25% Si, 0.4% Fe, 0.15% Cu, 0.8% Mn, 0.1% Cr, 4% Mg, 0.15% Zn, 0.02% Ti, 0.02% Sr, 0.05% Mo, 0.0005% Be, other unavoidable impurities and the balance Al.

[0108] The homogenization treatment temperature in this example is 450° C. and the holding time is 10 h. Example 5

[0109] This example is basically the same as Example 1, the only difference being the aluminum alloy composition and the temperature and time of the homogenization treatment in step (2).

[0110] Measured in percentage by mass, the B6 alloy provided in this example contains 0.25% Si, 0.45% Fe, 0.15% Cu, 0.75% Mn, 0.1% Cr, 4% Mg, 0.15% Zn, 0.02% Ti, 0.05% Sr, 0.02% Mo, 0.0005% Be, other unavoidable impurities and the balance Al.

[0111] The homogenization temperature in this example is 460°C and the holding time is 6 hours. Example 6

[0112] This example is basically the same as Example 1, the only difference being the aluminum alloy composition and the temperature and time of the homogenization treatment in step (2).

[0113] Measured in percentage by mass, the B7 alloy provided in this example contains 0.25% Si, 0.5% Fe, 0.2% Cu, 0.65% Mn, 0.15% Cr, 4% Mg, 0.2% Zn, 0.02% Ti, 0.05% Sr, 0.1% Mo, 0.0005% Be, other unavoidable impurities and the balance Al.

[0114] The homogenization treatment temperature in this example is 480° C. and the holding time is 4 h. Example 7

[0115] This example is basically the same as Example 1, the only difference being the aluminum alloy composition and the temperature and time of the homogenization treatment in step (2).

[0116] Measured in percentage by mass, the B8 alloy provided in this example contains 0.25% Si, 0.55% Fe, 0.3% Cu, 0.5% Mn, 0.15% Cr, 4% Mg, 0.2% Zn, 0.02% Ti, 0.1% Sr, 0.05% Mo, 0.0005% Be, other unavoidable impurities and the balance Al.

[0117] The homogenization treatment temperature in this example is 480° C. and the holding time is 2 h.

[0118] Performance Testing

[0119] According to the microstructure inspection method specified in the national standard GB / T3246.1, the aluminum alloy ingots obtained in step (1) of each embodiment and comparative example were inspected, wherein: Figure 1 is the as-cast structure diagram of the aluminum alloy ingot of Comparative Example 1, Figure 2 is the as-cast structure diagram of the aluminum alloy ingot of Comparative Example 3, Figures 3 to 9 The as-cast structure diagrams of the aluminum alloy ingots of Examples 1 to 7 are respectively, Figures 10 to 13 The statistical results of the area percentage and equivalent diameter of the Fe-rich phase and Mg2Si phase in the alloy cast structure are given respectively. The image analysis software was used to count the area percentage of the Fe-rich phase and Mg2Si phase in the metallographic photographs at 200X magnification. To ensure the accuracy of the statistical results, at least 5 fields of view were selected for statistics, and the average value was taken as the final result. The equivalent diameter of the Fe-rich phase and Mg2Si phase was calculated by the same method, and the area of ​​each second phase particle was counted respectively, and then according to S=πr 2 The equivalent diameter of each second phase particle is calculated. To ensure the accuracy of the statistical results, at least 200 second phase particles are counted and the average value is taken as the final result.

[0120] It can be seen that the conventional AA5182 alloy cast structure contains only a small amount of Mg2Si phase and iron-rich phase, which is related to its low Fe, Si, and Mn content. Compared with the AA5182 alloy, the Fe-rich phase content and equivalent diameter of the B1 alloy with high Fe and Mn content are increased to about 4.2% and 5.6μm respectively, and the coarse second phase particles will seriously damage the forming performance of the alloy. As for the B2~B8 alloys, although the alloys are prepared by recycled materials like the B1 alloy, so they contain a large amount of Fe and Mn elements, the B2~B8 alloys are optimized by alloy composition, especially by using the synergistic effect of Sr, Mo and Be elements with other elements, which changes the solidification behavior of the alloy, and its cast structure changes significantly. The content and equivalent diameter of the Fe-rich phase and Mg2Si phase in the alloy are significantly reduced compared with the B1 alloy. It shows that the high Fe content 5XXX aluminum alloy described in the present invention can further reduce and refine the content and size of the iron-rich phase and Mg2Si phase in the alloy by optimizing the alloy composition.

[0121] Figures 14 to 24 Metallographic photographs of the ingots after homogenization treatment in step (2) of comparative examples 1 to 4 and embodiments 1 to 7 are given respectively. Although the AA5182 alloy has extremely low Si and Fe contents, the iron-rich phase and Mg2Si phase cannot be completely dissolved after homogenization, and the content of the Mg2Si phase even tends to increase. The regenerated B1 alloy also has the same change pattern, and due to the increase in its Fe, Mn, and Si element content, the content and size of the iron-rich phase and Mg2Si phase in the alloy are significantly increased compared with the AA5182 alloy, and the homogenization treatment cannot eliminate them. However, the B2~B8 alloys produced by the embodiment method have a significantly lower content of the iron-rich phase after homogenization compared with the cast alloy, and the Mg2Si phase is fully dissolved.

[0122] Fig.25 The statistical results of the equivalent diameter of the iron-rich phase in the aluminum alloy after rolling are shown. A large rolling deformation is used during the rolling process to further break the primary second phase particles into smaller particles, thereby significantly improving the forming performance. The average equivalent diameter of the second phase particles of the B2~B8 alloys produced by the method of the present invention after rolling is ≤1.6μm. Although the B1 alloy also uses the same rolling process, it is extremely difficult to fully break and retain it during the subsequent processing because the initial Fe-rich phase and Mg2Si are relatively large in size. The alloy described in the present invention combines alloy composition optimization with homogenization and rolling processes, so that the coarse second phase particles are fully broken, weakening their influence on strength and plasticity.

[0123] The cold-rolled final thickness product is annealed and the plate is processed to the O state to obtain the final product. The final product is tested for tensile properties according to ISO 6892-1:2019 standard, and the results are shown in Table 1, where A50 It is the elongation after fracture of a standard tensile specimen with a gauge length of 50 mm. From Table 1, it can be seen that the strength of the B2~B8 alloys produced by the method described in the present invention is higher than that of the AA5182-O alloy, and the plasticity is equivalent. Although the strength of the B1 alloy of the recycled 5XXX series automotive sheet is slightly higher than that of the 5182-O alloy, its plasticity is significantly reduced.

[0124]

[0125] In summary, the Al-Mg aluminum alloy with high Fe and Mn content implemented in the present invention can be produced by using recycled cans, recycled automobile sheets, etc. as raw materials through alloy composition optimization, melting, homogenization, hot rolling, cold rolling, and annealing processes. It has higher strength and higher formability than AA5182, and can be used to prepare automobile body inner panels, structural parts, or rail transportation vehicles. In addition, the aluminum alloy described in the present invention itself has extremely high recyclability, which effectively reduces carbon emissions.

[0126] The above detailed description of the present invention is intended to enable persons familiar with the art to understand the contents of the present invention and implement them. It does not limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A 5XXX aluminum alloy, characterized in that: In terms of mass percentage, it includes Si 0.1-0.4%, Fe 0.35-0.6%, Cu 0.05-0.3%, Mn 0.4-0.9%, Mg 3.5-5.0%, Cr 0.05-0.3%, Zn 0-0.25%, Sr 0.01-0.15%, Mo 0.01-0.15%, Be 0.0001-0.001%, Ti≤0.15%, other impurities≤0.15%, the balance is Al; The preparation method of the 5XXX aluminum alloy comprises the following steps: (1) Using waste aluminum as raw material, selectively adding one or more of Al-Mn, Al-Cr, Al-Mo, Mg ingots, Al-Sr, and Al-Be master alloys, and sequentially performing smelting, slagging, alloying, refining, and casting to obtain aluminum alloy ingots; (2) subjecting the aluminum alloy ingot to a homogenization treatment, controlling the homogenization treatment temperature to be 420 to 480° C., and holding the temperature for 2 to 12 hours; (3) performing hot rough rolling on the aluminum alloy ingot after homogenization treatment, and controlling the deformation amount to be greater than 86%; (4) performing hot finish rolling on the hot rolled material after hot rough rolling, and controlling the deformation amount to be greater than 80%; (5) cold rolling the hot rolled material after hot finish rolling, and controlling the deformation amount to 65-93%; (6) Annealing the cold-rolled material after cold rolling to obtain the 5XXX aluminum alloy.

2. The 5XXX aluminum alloy of claim 1, wherein: Calculated by mass percentage, it includes Si 0.2-0.3%, Fe 0.4-0.55%, Cu 0.05-0.3%, Mn 0.45-0.85%, Mg3.5-4.5%, Cr 0.05-0.3%, Zn 0-0.25%, Sr 0.01-0.15%, Mo 0.01-0.15%, Be 0.0001-0.001%, Ti≤0.15%, other impurities≤0.15%, and the balance is Al.

3. The 5XXX aluminum alloy according to claim 1 or 2, characterized in that: The mass percentage of Sr is 0.02-0.1%, and the mass percentage of Mo is 0.02-0.1%.

4. The 5XXX aluminum alloy according to claim 1 or 2, characterized in that: The total mass percentage of the Sr and Mo does not exceed 0.15%.

5. The 5XXX aluminum alloy according to claim 1 or 2, characterized in that: The total mass percentage of the Mn, Mg and Cu is ≥4%.

6. The 5XXX aluminum alloy of claim 1 or 2, wherein: The mass ratio of the total mass of the Mn and the Cr to the Fe is 1:1 to 3:

1.

7. The 5XXX aluminum alloy of claim 1 or 2, wherein: The mass ratio of the total mass of the Sr and the Mo to the mass of the Si is 1:20 to 1:1.

5.

8. The 5XXX aluminum alloy of claim 1, wherein: The tensile strength of the 5XXX aluminum alloy is Rm≥330MPa, and the plastic extension strength R p0.2 ≥180MPa, elongation after fracture A 50 ≥22%.

9. The 5XXX aluminum alloy of claim 1, wherein: The average equivalent diameter of the iron-rich phase in the 5XXX aluminum alloy is ≤1.6 μm.

10. The 5XXX aluminum alloy of claim 1, wherein: The 5XXX aluminum alloy is an O-state aluminum alloy.

11. A method for preparing a 5XXX aluminum alloy as claimed in any one of claims 1 to 10, characterized in that: It includes the following steps: (1) Using waste aluminum as raw material, selectively adding one or more of Al-Mn, Al-Cr, Al-Mo, Mg ingots, Al-Sr, and Al-Be master alloys, and sequentially performing smelting, slagging, alloying, refining, and casting to obtain aluminum alloy ingots; (2) subjecting the aluminum alloy ingot to a homogenization treatment, controlling the homogenization treatment temperature to be 420 to 480° C., and holding the temperature for 2 to 12 hours; (3) performing hot rough rolling on the aluminum alloy ingot after homogenization treatment, and controlling the deformation amount to be greater than 86%; (4) performing hot finish rolling on the hot rolled material after hot rough rolling, and controlling the deformation amount to be greater than 80%; (5) cold rolling the hot rolled material after hot finish rolling, and controlling the deformation amount to 65-93%; (6) Annealing the cold-rolled material after cold rolling to obtain the 5XXX aluminum alloy.

12. The preparation method according to claim 11, characterized in that: The waste aluminum is one or more of recycled cans, automobile plates, and ship plates.

13. The preparation method according to claim 11, characterized in that: In step (1), the area percentage of the iron-rich phase in the aluminum alloy ingot is controlled to be ≤3.5%, and the average equivalent diameter is ≤3.5 μm; the area percentage of the Mg2Si phase is controlled to be ≤1.6%, and the average equivalent diameter is controlled to be ≤1.2 μm.

14. Use of the 5XXX aluminum alloy according to any one of claims 1 to 10, or the 5XXX aluminum alloy prepared by the preparation method according to any one of claims 11 to 13 in automobile body inner panels, structural parts or rail transportation structural parts.

Citation Information

Patent Citations

  • 5182 aluminum alloy and technology method for preparing tank cover material strip through aluminum alloy

    CN106834825A

  • Al-Mg-Si-Sn-RE series rare earth aluminum alloy, preparation method thereof and heat-resistant cable

    CN117305668A

  • High-strength aluminum alloys for can end stock and methods for preparing the same

    WO2023215308A1

Cited By

  • Low-carbon recycled aluminum alloy plate and preparation method thereof

    CN122648757A